Comparative Analysis of Trigeminal Neuralgia Caused by Sole Arterial and Venous Compression: Clinical Features and Surgical Outcomes From 222 Cases - Wang, Junwen; Niu, Hongquan; Zhao, Kai; Shu, Kai; Lei, Ting (Frontiers in Neurology, 2021)
Background Compared with trigeminal neuralgia (TN) caused by arterial neurovascular conflict (NVC), the clinical characteristics and managements for TN with venous NVC are not well established. This study aims to comparatively summarize the clinical features and surgical outcomes of microvascular decompression (MVD) for TN patients caused by sole arterial and venous compression, with a particular focus on the morphological features of PCF. Methods 222 TN patients caused by sole arterial NVC (188/84.7%) and venous NVC (34/15.3%) underwent MVD in our department from January 2014 to December 2018. The patient data were analyzed retrospectively. Particularly, we focused on the potential impact of posterior cranial fossa (PCF) on surgical outcomes. Results Compared to arterial NVC, V3-branch of the trigeminal nerve was more frequently involved in venous NVC (p=0.009). The most common compression site was root entry zone for arterial NVC (68.6%) and mid-cisternal segment for venous NVC (76.5%) (p＜0.001). No serious postoperative complication was observed in the two groups. Both short- and long-term outcomes were relatively worse in venous NVC cases compared to arterial NVC cases (p=0.001 and p=0.030, respectively); and a dominantly higher rate of delayed cure was demonstrated in venous NVC cases (p＜0.001). TN patients with venous NVC revealed a more flat-shaped PCF compared to those with arterial NVC. Moreover, flat-shape PCF morphometry was negatively correlated with surgical outcomes of TN patients with arterial NVC, but not with those of venous NVC cases. Conclusions MVD is an effective and safe treatment for TN patients caused by either arterial or venous NVC. Patients with a more flat-shaped PCF might be vulnerable to venous compression. Our study demonstrated that PCF morphometry only affected the surgical outcomes of TN patients caused by arterial NVC, but not the outcomes of those with venous NVC.